2002
DOI: 10.1152/ajplung.00112.2001
|View full text |Cite
|
Sign up to set email alerts
|

Platelets inhibit the lysis of pulmonary microemboli

Abstract: Using tracings of 125 I-labeled fibrin(ogen) in rodents, we examined the hypothesis that platelets impede the lysis of pulmonary emboli.125 I-Microemboli (ME, 3-10 micron diameter) lodged homogeneously throughout the lungs after intravenous injection in both rats and mice (60% of injected dose), caused no lethality, and underwent spontaneous dissolution (50 and 100% within 1 and 5 h, respectively). Although lung homogenates displayed the most intense fibrinolytic activity of all the major organs, dissolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…3b). The correlation coefficient (r ¼ 0.734) confirmed a sound concurrence with confocal microscopy studies of model clots in vitro, where platelets were shown to impede the transport of thrombolytics into the clot (24,27). The correlation could serve for estimation of thrombolysis outcome if the initial platelet proportion is known.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…3b). The correlation coefficient (r ¼ 0.734) confirmed a sound concurrence with confocal microscopy studies of model clots in vitro, where platelets were shown to impede the transport of thrombolytics into the clot (24,27). The correlation could serve for estimation of thrombolysis outcome if the initial platelet proportion is known.…”
Section: Discussionsupporting
confidence: 71%
“…Aged thrombi may contain also collagen type III that increases their compactness and impairs the response to thrombolysis (26). Further discrepancies in dissolution properties can be attributed to inefficient perfusion into the thrombus due to platelet coalescence, that is, Zahn lines, which impede the transport of the thrombolytic agent (27). In our study, platelet laminations were often found near the surface of thrombi, thus preventing efficient permeation of plasma containing rt-PA into the deeper layers (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…However, prophylactic fibrinolysis by PECAM-targeted PA may help to prevent extension/recurrence of pulmonary thromboembolism 32,46 and attenuate acute lung graft rejection because of thrombotic occlusion of the pulmonary vasculature. 47 Because of the pan-endothelial nature of PECAM expression and the opportunity to enrich local delivery using catheters, 17 a wider utility to protect other vascular beds against imminent thrombosis can be envisioned.…”
Section: Discussionmentioning
confidence: 99%
“…10,32 One hour later, mice were killed and residual isotope was measured in the lungs. As in previous studies, 10,32 spontaneous dissolution of emboli in control mice at this time was approximately 50%.…”
Section: Prophylactic Fibrinolysis In a Model Of Pulmonary Embolismmentioning
confidence: 99%
See 1 more Smart Citation